BUDIDAYA MELON RAMAH LINGKUNGAN DI AREA SEKITAR GUMUK PASIR - PURNOMO, BUDI SETIADI DARYONO (Prodi Pendidikan Biologi FKIP UNS, 2014)
Coastal area around sand dune on the Bocor Beach potentially used as agricultural land especially melon cultivation. It was located at Buluspesantren Subdistric , Kebumen Distric, Central Java. Cultivation techniques in that land were not green cultivation .The use of pesticides, non-organic material, and plant cutting in the area of sand dune have a potential to damage the environment. This event was aimed to introduce the technique of green melon cultivation so that melon cultivation around sand dune can develop and sustainable. The technique of melon cultivation used in this activity was production of melon superior seed and fruit selection. Melodi Gama3 (MG3) was one of the superior seed which used in this activity. Superior seed was able to reduce the use of pesticides and fruit selection can produce fruit in a high quality. Then the group of farmers trained to use local potential as a substitute for a common material used by other farmers. Palm midrib instead of bamboo, pandanus fiber as a rope replacement, and some other potential materials can be used. Cultivation techniques are transfered to farmers group by training and farmers models. The results of economic analysis indicates that the green melon cultivation techniques are able to increase the income of farmers in the area melon around sand dune. After this event, the farmers was expected to develop environmentally welfare farming techniques in the area around sand dune in Bocor Beach. Keywords: Sustainable development, melon cultivation, sand dune